A multivalent Plasmodium falciparum circumsporozoite protein‐based nanoparticle malaria vaccine elicits a robust and durable antibody response against the junctional epitope and the major repeats - Geetanjali Pendyala; J. Mauricio Calvo‐Calle; Alberto Moreno; Ravi S. Kane (Wiley, 2023)
Abstract Plasmodium falciparum (Pf) malaria continues to cause considerable morbidity and mortality worldwide. The circumsporozoite protein (CSP) is a particularly attractive candidate for designing vaccines that target sporozoites-the first vertebrate stage in a malaria infection. Current PfCSP‐based vaccines, however, do not include epitopes that have recently been shown to be the target of potent neutralizing antibodies. We report the design of a SpyCatcher‐mi3‐nanoparticle‐based vaccine presenting multiple copies of a chimeric PfCSP (cPfCSP) antigen that incorporates these important "T1/junctional" epitopes as well as a reduced number of (NANP)n repeats. cPfCSP‐SpyCatcher‐mi3 was immunogenic in mice eliciting high and durable IgG antibody levels as well as a balanced antibody response against the T1/junctional region and the (NANP)n repeats. Notably, the antibody concentration elicited by immunization was significantly greater than the reported protective threshold defined in a murine challenge model. Refocusing the immune response toward functionally relevant subdominant epitopes to induce a more balanced and durable immune response may enable the design of a more effective second generation PfCSP‐based vaccine.